2011
DOI: 10.1111/j.1469-8137.2010.03606.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and regulation of iron‐regulated metal transporters in Arabidopsis halleri and Arabidopsis thaliana – the role in zinc tolerance

Abstract: To avoid zinc (Zn) toxicity, plants have developed a Zn homeostasis mechanism to cope with Zn excess in the surrounding soil. In this report, we uncovered the difference of a cross-homeostasis system between iron (Fe) and Zn in dealing with Zn excess in the Zn hyperaccumulator Arabidopsis halleri ssp. gemmifera and nonhyperaccumulator Arabidopsis thaliana. Arabidopsis halleri shows low expression of the Fe acquisition and deficiency response-related genes IRT1 and IRT2 compared with A. thaliana. In A. thaliana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 68 publications
16
112
1
11
Order By: Relevance
“…Under these treatments, the wild-type plants survived excessive zinc from 50 to 200 lM, but not above this upper limit ( Figure S4). These results are similar to the findings of Shanmugam et al(2011). Our results showed that seedlings given 50 lM of iron and treated with 30 lM of zinc resulted in chlorotic symptoms of iron deficiency in yid1 compared with the wild-type plants which showed normal growth ( Figure 2b).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Under these treatments, the wild-type plants survived excessive zinc from 50 to 200 lM, but not above this upper limit ( Figure S4). These results are similar to the findings of Shanmugam et al(2011). Our results showed that seedlings given 50 lM of iron and treated with 30 lM of zinc resulted in chlorotic symptoms of iron deficiency in yid1 compared with the wild-type plants which showed normal growth ( Figure 2b).…”
Section: Resultssupporting
confidence: 82%
“…In Arabidopsis, excessive zinc resulted in iron-deficient chlorosis, which can be reversed using excess iron; this is known as the iron-mediated zinc tolerance mechanism (Shanmugam et al, 2011). To test whether yid1 was hypersensitive to excessive zinc when the iron balance was disrupted, we treated yid1 and wild-type seedlings with excessive zinc and different iron concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its role in Fe acquisition, AtIRT1 is also responsible for the uptake of Zn from the soil solution (Fukao et al, 2011). The broad selectivity of AtIRT1 allows this transporter to mediate the uptake of several divalent metal cations, including Zn (Barberon et al, 2011;Shanmugam et al, 2011). This was also demonstrated in rice plants overexpressing OsIRT1, which accumulate elevated levels of Zn in the shoots, roots and mature seeds ).…”
Section: Zinc Uptake By Plantsmentioning
confidence: 99%
“…Upon conversion to a plant-usable form, Fe, Cu, Mn, but also Zn and Ni, are transported into the plant. This process, again, could occur through a shared uptake system involving similar divalent metal transporting enzymes (e.g., ironregulated transporter, IRT) that are present in both root and shoot cells (Connolly et al 2002(Connolly et al , 2003Ishimaru et al 2005;Kim and Guerinot 2007;Shanmugam et al 2011;Sinclair and Krämer 2012). In some plants, the exudation from the root of different metal-binding compounds such as phytosiderophores and organic acids results in the uptake of Fe, Cu, Zn, Ni, and Mn, often by similar metal-binding compounds (Schaaf et al 2004;Keuskamp et al 2015).…”
Section: Agronomic Role (Ii): Enhancement Of the Efficiency Of Npkmentioning
confidence: 99%